"Nature Was Helping Us": Forests, Trees, and Environmental Histories of the Holocaust. (24th September 2014) - Cole, Tim
Abstract: This article explores what environmental history might contribute to the field of holocaust and genocide studies (and environmental histories of genocide might contribute to the field of environmental histories of war) through examining the complex ways nature functioned materially and imaginatively during the Holocaust and its postwar telling. Drawing on both published and unpublished memoirs and oral history interviews with Jews who survived the war hiding in the forests of central and eastern Europe, the article examines three main tensions. First, they experienced the woods as a disorienting, alien, and alienating world, and yet an escape from a more corrupt world outside the forest. Second, nature was both something to be worked with and adapted to given its benevolent role while also being seen as insufficient and therefore in need of supplementing in order to survive. Third, adapting to nature—or becoming "animal" as a number of survivors put it—was both assertion of successful survival and a way of explaining and distancing self from wartime behavior in the forest. While survivors have told stories of human triumph over nature, they have also told stories of "nature" acting on their behalf.